Escravos e imigrantes são o que importam: fornecimento e controle da mão de obra para a economia agroexportadora Oitocentista - Gonçalves, Paulo Cesar (Universidade Federal de São Paulo - UNIFESP, 2017)
Abstract Throughout the nineteenth century, the new configuration of the world economy reserved the role of producer and exporter of coffee for Brazil, resulting in expansion of crops and increase in the demand for hands: initially slaves, then immigrants. In the context of the transition from slave to free labor the article intends to analyze comparatively the strategies developed by large landowners and by the State to obtain and control the labor destined for coffee plantations.

Resumo Ao longo do século XIX, a nova configuração da economia mundial reservou ao Brasil o papel de produtor e exportador de café, resultando na expansão das lavouras e no aumento da demanda por braços: inicialmente escravos, depois imigrantes. No contexto da transição do trabalho escravo para o livre, o artigo pretende analisar de forma comparativa as estratégias desenvolvidas por grandes proprietários de terras e pelo Estado para obtenção e controle da mão de obra destinada às plantações de café.
Slaves and immigrants are what matter: sourcing and control of the workforce for the agro-exporting economy in the Eighteenth Century
Keywords: Slavery; Free Labor; Coffee Economy; Escravidão; Trabalho Livre; Economia Cafeeira